Quantum Chemical Topological Analysis of [2Fe2S] Core in Novel [FeFe]-Hydrogenase Mimics - Piotr Matczak (Crystals)
Synthetic mimics of the active site of [FeFe]-hydrogenase enzymes are important in the context of catalytic hydrogen production for future energetic applications. Providing a detailed quantum chemical description of the catalytic center of such mimics contributes to a better understanding of their behavior in hydrogen production processes. In this work, the analysis of bonds in the butterfly [2Fe2S] core in a series of complexes based on recently synthesized [FeFe]-hydrogenase mimics has been carried out using a wide range of quantum chemical topological methods. This series includes hexacarbonyl diiron dithiolate-bridged complexes with the bridging ligand bearing a five-membered carbon ring functionalized with diverse groups. The quantum theory of atoms in molecules (QTAIM) and the electron localization function (ELF) provided detailed characteristics of Fe–Fe and Fe–S bonds in the [2Fe2S] core of the complexes. A relatively small amount of strongly delocalized electron charge is attributed to the Fe–Fe bond. It was established how the topological parameters of the Fe–Fe and Fe–S bonds are affected by the five-membered carbon ring and its functionalization in the bridging dithiolate ligand. Next, one of the first applications of the interacting quantum atoms (IQA) method to [FeFe]-hydrogenase mimics was presented. The pairwise interaction between the metal centers in the [2Fe2S] core turns out to be destabilizing in contrast to the Fe–S interactions responsible for the stabilization of the entire core.